Sphingolipid metabolic flow controls phosphoinositide turnover at the trans‐Golgi network. (11th May 2017) - Capasso, Serena; Sticco, Lucia; Rizzo, Riccardo; Pirozzi, Marinella; Russo, Domenico; Dathan, Nina A; Campelo, Felix; van Galen, Josse; Hölttä‐Vuori, Maarit; Turacchio, Gabriele; Hausser, Angelika; Malhotra, Vivek; et al.
Abstract: Sphingolipids are membrane lipids globally required for eukaryotic life. The sphingolipid content varies among endomembranes with pre‐ and post‐Golgi compartments being poor and rich in sphingolipids, respectively. Due to this different sphingolipid content, pre‐ and post‐Golgi membranes serve different cellular functions. The basis for maintaining distinct subcellular sphingolipid levels in the presence of membrane trafficking and metabolic fluxes is only partially understood. Here, we describe a homeostatic regulatory circuit that controls sphingolipid levels at the trans ‐Golgi network (TGN). Specifically, we show that sphingomyelin production at the TGN triggers a signalling pathway leading to PtdIns(4) P dephosphorylation. Since PtdIns(4) P is required for cholesterol and sphingolipid transport to the trans ‐Golgi network, PtdIns(4) P consumption interrupts this transport in response to excessive sphingomyelin production. Based on this evidence, we envisage a model where this homeostatic circuit maintains a constant lipid composition in the trans ‐Golgi network and post‐Golgi compartments, thus counteracting fluctuations in the sphingolipid biosynthetic flow. Synopsis: Sphingolipid production at the trans ‐Golgi network triggers a PtdIns(4) P level‐dependent negative feedback loop that ensures maintenance of distinct post‐Golgi endomembrane sphingolipid content and thus counterbalances alterations in lipid metabolic fluxes. PtdIns(4) P levels at the Golgi complex are negatively regulated by ceramide transport to the TGN and by local sphingomyelin synthesis. Ceramide transport to the TGN and local sphingomyelin synthesis promote OSBP1‐mediated non‐vesicular transport of PtdIns(4) P to the ER for Sac1‐dependent dephosphorylation. The localization of PtdIns(4) P effectors and non‐vesicular ceramide/sphingomyelin transporters CERT and FAPP2 at the TGN is negatively regulated by reduced PtdIns(4) P levels. As a consequence, sphingomyelin synthesis at the TGN inhibits local sphingomyelin and complex glycosphingolipids production as well as their enrichment at post‐Golgi membranes. Abstract : Sphingolipid production at the trans ‐Golgi network triggers a PtdIns(4) P level‐dependent negative feedback loop that ensures maintenance of distinct post‐Golgi endomembrane sphingolipid content and thus counterbalances alterations in lipid metabolic fluxes.